Sobre Pablo Escalante Gonzalbo, Pilar Gonzalbo Aizpuru, Anne Staples, Engracia Loyo Bravo, Cecilia Greaves Lainé y Verónica Zárate Toscano, Historia mínima. La vida cotidiana en México - Peña Díaz, Manuel (Historia Mexicana, 2012)
-